(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Plants with medicinal properties are frequently used to treat infertility in developing nations like Nigeria. One of such herbs, Annona senegalensis, is traditionally used to treat male fertility issues.The present study investigated its fertility enhancement claims.25 Wister rats divided into 5 groups A – E, were used for the study. Groups B – E were given 100 mg/kg, 200 mg/kg, 300 mg/kg and 400 mg/kg of the ethanolic leaf extract respectively while Group A served as control. The extract was administered for 28 days thereafter semen samples from each group were analyzed weekly for 4 weeks. At the 4th week; some enzyme, hormonal and bilirubin assays were carried out. Result showed semen characteristics such as motility, sperm concentration and normal sperm morphology were significantly (P<0.05) increased in treated Groups (B – E). Testosterone increased significantly (P<0.05) in treated Groups compared with Control. While Follicle stimulating hormone and Luteinizing hormone were lower. AST increased in numerical mean values while ALK reduced compared with the control. ALT varied insignificantly. Bilirubin did not differ significantly. These findings suggest male fertility enhancement potentials as claimed by African folklore medical practices. Hence more studies are recommended to further substantiate and elucidate its pharmacological activities.